The Effect of Self-regulated Strategy Instruction and Behavioral Consultation on Motivation: A Longitudinal Study on the Effect of School-Based Interventions in Secondary Education - Minnaert, Alexander; Prince, Arnout; Opdenakker, Marie-Christine (Frontiers in Education, 2017)
Studies show a decrease in students’ motivation in secondary education. Hence it was investigated whether training of teachers could stop this decline. Two interventions were implemented in pre-vocational secondary education, being self-regulated strategy instruction and behavioral consultation combined with strategy instruction. The longitudinal effects of the two interventions were tested on the goal orientations of 279 students. The growth curves show a long term effect of the intervention combining teacher consultancy with strategy instruction on task orientation, ego-enhancing orientation and ego-defeating orientation as compared to the control condition. For the strategy instruction only condition, only effects on ego orientation were found. The outcomes suggest that combining the instruction of self-regulation strategies with teacher consultation on student problem-solving can stop the downward trend in student motivation, even on the long term.